2020
DOI: 10.1097/yic.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA for the treatment of major depressive disorder: a phase 2 randomized, double-blind, placebo-controlled trial in adult females

Abstract: This 24-week double-blind placebo-controlled multicenter randomized phase 2 trial evaluated efficacy and safety of onabotulinumtoxinA (onabotA; BOTOX) vs. placebo for major depressive disorder (MDD) [NCT02116361]. Primary endpoint was the change in Montgomery-Åsberg Depression Rating Scale (MADRS); secondary endpoints were Clinical Global Impressions-Severity and 17-item Hamilton Depression Rating Scale at week 6. A total of 255 adult females were treated. OnabotA 30 U approached significance compared to place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 39 publications
3
55
0
3
Order By: Relevance
“…In the last decade, several randomized double-blind placebo-controlled clinical trials 11,[28][29][30] , case series 31 , and an open-label study 32 have demonstrated significant efficacy of BoNT injections into the glabellar region of the face in treating depression. These studies were followed by a larger, industry-sponsored Phase II trial with 258 participants however the results were mixed 12 . Although there was a decrease in depression rating scores and numeric superiority of BoNT over placebo, the results did not meet the primary endpoint criteria.…”
mentioning
confidence: 99%
“…In the last decade, several randomized double-blind placebo-controlled clinical trials 11,[28][29][30] , case series 31 , and an open-label study 32 have demonstrated significant efficacy of BoNT injections into the glabellar region of the face in treating depression. These studies were followed by a larger, industry-sponsored Phase II trial with 258 participants however the results were mixed 12 . Although there was a decrease in depression rating scores and numeric superiority of BoNT over placebo, the results did not meet the primary endpoint criteria.…”
mentioning
confidence: 99%
“…Twentythree articles were excluded; the reasons are presented in Figure 1. Finally, five RCTs met the inclusion criteria for this meta-analysis (13)(14)(15)(16)24).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…We identified five eligible articles involving a total of 417 participants (189 patients in the BTX-A group, 228 patients in the placebo group), all of which were randomized, placebocontrolled trials published between 2012 and 2020. Notably, Brin et al (16) carried out a two-dose parallel groups study of low dosage (30 U) and high dosage (50 U) BTX-A. There were 389 females and 28 males, with a mean (SD) sample size of 70 (44.0) and a mean (SD) age of 46.4 (4.1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations